Model of strategic analysis and formulation. Using matrix tools - Acevedo Borrego, Adolfo (2010)
The analysis and strategic formulation is a strategic assessment and preparation process of designing the future of industry, business or enterprise. The goal is to develop some elements for discussion and unification of several directives conceptions. The phases of strategic analysis are five: 1) Input phase, summarizes initial data and raises the company’s strategic position and products, 2) Analysis phase, integrates external and internal factors and raises strategic alternatives, 3) Output phase consolidate all strategies considering their technical feasibility, 4) Qualifying phase of the alternatives that fulfill the condition F + D and create value, 5) Evaluation and decision, choosing strategies that deliver value to the company. The expected result considers that, from an initial situation where analysis and long-term projection of insufficient or non-existent it passes to new situation where it has right tools for the preparation and choice of strategies feasible and desirable.